Glomangioma of the Kidney: A Rare Case of Glomus Tumor and Review of the Literature. (18th June 2017) - Almaghrabi, Ammar; Almaghrabi, Nizar; Al-Maghrabi, Haneen
Abstract : Background . Glomus tumors are rare mesenchymal tumors originating from glomus bodies in the skin. Glomus tumors of the kidney are rare tumors and only a few cases have been reported in the medical literature. An extensive search revealed a very limited number of primary renal glomus tumors. Although most of these cases were benign in nature, including a case with uncertain diagnosis of malignant potential, two were malignant. Case Report . We present a unique case of a 57-year-old male patient with an incidentally discovered 2 cm left renal mass. Histopathology examination and immunohistochemical studies confirm the diagnosis of glomangioma (a form of glomus tumor). The patient was followed for one year after partial nephrectomy and showed a benign course without any evidence of local recurrence or metastasis. Conclusion . To the best of our knowledge, this is the 16th case of primary benign renal glomus tumors. Primary renal glomus tumors are rare and may mimic other mesenchymal renal neoplasms radiologically. Proper investigation (including histopathological analysis and immunohistochemical staining) of kidney tumors is essential to make the diagnosis of glomus tumors, which usually show a benign clinical course following resection.